1986
DOI: 10.1104/pp.82.2.479
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of a Novel Nicotine Alkaloid in the Trichomes of Nicotiana stocktonii

Abstract: N-Hydroxyacylnornicotine, newly discovered from fresh plant tissue, was found entirely in the trichome exudate produced at the epidermis of the aerial part of Nicotiana stocktonii. Nicotine and nornicotine, but not N-hydroxyacylnornicotine, were present inside of the trichomes as well as other internal parts of the plant. Only nicotine was found in bleeding sap squeezed from cut roots or stems. Feeding of leaves with 2'-'4C-labeled nicotine primarily yielded labeled nicotine, nornicotine, and Nhydroxyacylnorai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Trichomes play a major role in plant defense mechanisms and are known to be important structural barriers protecting plants from insect herbivory (Fernandes, 1994;Traw and Dawson, 2002). Indeed, trichomes have been found to both accumulate and excrete many toxic chemicals known to inhibit herbivory, such as various alkaloids and other plant secondary compounds (Rodriguez et al, 1984;Cutler et al, 1986;Zador and Jones, 1986). Many plant species respond to insect damage by increasing the density and/or number of trichomes on new leaves (Myers and Bazely, 1991;Traw, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomes play a major role in plant defense mechanisms and are known to be important structural barriers protecting plants from insect herbivory (Fernandes, 1994;Traw and Dawson, 2002). Indeed, trichomes have been found to both accumulate and excrete many toxic chemicals known to inhibit herbivory, such as various alkaloids and other plant secondary compounds (Rodriguez et al, 1984;Cutler et al, 1986;Zador and Jones, 1986). Many plant species respond to insect damage by increasing the density and/or number of trichomes on new leaves (Myers and Bazely, 1991;Traw, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, tobacco species are known to contain the toxins nicotine and related alkaloids. Nicotine itself is synthesized in the roots and is mobilized to all aerial parts of the plant, including trichomes, upon herbivory (Zador and Jones, 1986). While nicotine predominates in roots, leaves and trichomes contain higher levels of nornicotine (demethylated nicotine) than of nicotine.…”
Section: Alkaloidsmentioning
confidence: 99%
“…2). Previous studies indicating that nornicotine is converted by nicotine in the leaf, were confirmed by 2′-14 C-labeled alkaloid feeding experiments (Zador and Jones, 1986). Siminszky et al (2005) found that the demethylation of nicotine to nornicotine was catalyzed by the cytochrome P450 enzyme CYP82E4.…”
Section: Genetic Variation In Alkaloid Accumulationmentioning
confidence: 60%